Intelligent Systems Technologies and Applications 2016 - Corchado Rodriguez, Juan Manuel; Mitra, Sushmita; Thampi, Sabu M.; El-Alfy, El-Sayed.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book constitutes the thoroughly refereed proceedings of the second International Symposium on Intelligent Systems Technologies and Applications (ISTA'16), held on September 21-24, 2016 in Jaipur, India. The 80 revised papers presented were carefully reviewed and selected from 210 initial submissions and are organized in topical sections on image processing and artificial vision, computer networks and distributed systems, intelligent tools and techniques and applications using intelligent techniques.
Image Processing and Artificial Vision -- Networks/ Distributed Systems -- Intelligent Tools and Techniques -- Applications using Intelligent Techniques.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence